Hakikat Belajar Dan Pembelajaran - Silviana Nur Faizah (Universitas Islam Lamongan, 2017)
Learning is a process that must be done by every individual to get knowledge. It is considerably a fundamental element in the implementation of any education level. The success of education depends on the student learning process both within and outside the school. In formal education the learning process is inseparable from to the teaching and learning process. Both of these processes are synergized to realize the ideals of the nation in order to educate the life of the world. As learning creatures and educational practitioners, whatever related to learning is important to know. Learning is a conscious activity undertaken by individuals through training and experiences that produce behavioral changes that include the cognitive, affective and psychomotor aspects. While teaching and learning is a system or process of teaching subject matters that are planned, implemented, and evaluated systematically so that students can achieve the learning objectives effectively and efficiently. Three learning characteristics are: (a) learning is a conscious effort of a person, (b) learning is characterized by a change of behavior that encompasses all aspects (cognitive, affective, and psychomotor), and such changes are relatively permanent, (c) changes in behavior are derived from the interaction process with the environment and exercises. Factors that influence learning and teaching process are internal factors (physiological and psychological) and external factors (family, school and community). Five principles of learning: subsumption, organizer progressive differentiation concolidation integrative Reconciliation.Keywords: Learning process, education, environment